Work of the board of judges when conducting competitions in athletics - Bollasov, A.K.; Mirzakhmedova, D.Sh. (Science and Education, 2024)
This article covers athletics competitions, the form of organization of athletics competitions, regulations on the competition, competition program, medical support for competitions, preparation of competition sites and equipment in accordance with the competition rules.